2004
DOI: 10.1039/b400944d
|View full text |Cite
|
Sign up to set email alerts
|

Novel setup for investigation of the plasma conditions in direct sample insertion inductively coupled plasma atomic emission spectrometry (DSI-ICP-AES)

Abstract: Insertion of a sample probe into the inductively coupled plasma (ICP) for direct sample insertion (DSI) could change the plasma excitation conditions. In this study, a novel setup is proposed for the investigation of the probe effects. A hollow graphite tube was used as a stand-in for the DSI sample probe to exert probe effects on the plasma. Laser-ablated testing elements (Fe, Zn and Mg) were introduced separately into the central channel of the plasma via the hollow graphite tube for measurement of plasma ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The potential of quadrupole ICPMS was studied as an alternative to X-ray spectrometry for the measurement of 129 I in environmental samples by Bienvenu et al (189). Although ICPMS exhibits attractive features for the measurement of this radionuclide, the occurrence of natural iodine 127 I at substantial levels in the solutions recovered after dissolution and extraction steps was shown to induce an interference on the 129 I signal, due to the formation of a polyatomic IH 2 species, as well as a substantial matrix effect for quantitative analyses.…”
Section: Inductively Coupled Plasma Mass Spectrometrymentioning
confidence: 99%
See 3 more Smart Citations
“…The potential of quadrupole ICPMS was studied as an alternative to X-ray spectrometry for the measurement of 129 I in environmental samples by Bienvenu et al (189). Although ICPMS exhibits attractive features for the measurement of this radionuclide, the occurrence of natural iodine 127 I at substantial levels in the solutions recovered after dissolution and extraction steps was shown to induce an interference on the 129 I signal, due to the formation of a polyatomic IH 2 species, as well as a substantial matrix effect for quantitative analyses.…”
Section: Inductively Coupled Plasma Mass Spectrometrymentioning
confidence: 99%
“…These difficulties were overcome by analyzing diluted solutions and using 133 Cs as internal standard. The use of ICPMS after sample pretreatment allowed detection limits for 129 I in the range of 10 -4 Bq/g (10 -11 g/g). The accuracy of the measurements was estimated in comparison with results obtained on the same samples by X-ray spectrometry.…”
Section: Inductively Coupled Plasma Mass Spectrometrymentioning
confidence: 99%
See 2 more Smart Citations
“…Cheung et al 216 have reported on the use of a hollow graphite tube as a surrogate for a direct sample insertion (DSI) probe in order to study the effects of DSI on plasma excitation. They found that T exc and n e increased on probe insertion, with the effect being strongest near the tip.…”
Section: Glow Discharges Arcs and Sparksmentioning
confidence: 99%